Effects of Architectural and Urban Design Project Competitions on Built Environment and New Discourses Brought Thereby - OSMAN UMIT Sirel; AYSE SIREL; BURAK TURSOY (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
The competition system is considered to be the most objective project selection method in a country’s architectural and urbanism organization and is a mechanism which promotes professional creativity. Both national and international competitions have significant potential in terms of providing knowledge and accumulation to contemporary architecture history. The aim of competitions is to obtain